The Effectiveness Of Flashcards And Word Cards In Improving Knowledge And Attitudes Worms; In The Elementary School Children - Maisje Marlyn Kuhu; Herry Prasetyo; Nuryamah Nuryamah (Jurnal Riset Kesehatan, 2013)
Background: As an educational institution, the school has a role and strategic position in health promotion efforts on the prevention of worms. One of the efforts made to protect from the disease. It is the provision of flashcards and word cards containing images and materials about the disease worms.Research goal: To investigate the effectiveness of flashcards and word cards in improving knowledge and attitudes about disease worms in the elementary school children in the village Karangduren.Method: The study was quasi-experimental (quasi experiment) with the study design before and after the intervention using a comparison group. The data obtained were processed using statistical test paired sample t test (paired t-test).Results: The results of statistical tests showed that using flashcard media is more effective than the use of the word as a media card media health promotion to improve the knowledge and attitudes about disease prevention due to worms in primary schools students 01 Karangduren Banyumas.